The Revitalization of The Culture and The Traditional Building of Rumah Godang in Kenegerian Adat Sentajo Kuantan Singingi - Zulfan Saam; Thamrin Thamrin; Nofrizal Nofrizal; Fachrurrozi Fachrurrozi (ECOTONE, 2021)
Rumah Godang or traditional house in Kuantan Singingi is a cultural heritage building. The building is tens or even hundreds of years old, but the building is still preserved. The existence of Rumah Godang is related to socio-cultural activities and environmentally friendly traditional tambul. Recently, there has been a degradation of the function of Rumah Godang and its socio-cultural activities. Therefore, it is necessary to revitalize the socio-culture and building of Rumah Godang. The purpose of this study was to develop a cultural revitalization program and to compile a technical drawing of the Rumah Godang building. This type of research is qualitative research. The research location is the customary state of Sentajo, Kuantan Singingi Regency. The study population was the traditional houses and cultural activities in Kenegerian adat Sentajo. Data collection techniques are through observation and in-depth interviews with key informants, namely traditional leaders and formal leaders which are then analyzed qualitatively. The results of this study are (a) Revitalization of cultural aspects is the socialization delivered by ninik mamak in Rumah Godang or other traditional events, (b) The arrangement of technical drawings of Rumah Godang keeps Rumah Godang original, so that if it is renovated it must be guided by technical drawings.